Absence of the Transcendental Signified: Tracing the Dynamics of Intertextuality in Selected Essays of Shoaib Bin Hassan - Rija Ahsan; Sarah Ishfaq (Linguistics and Literature Review, 2021)
This research aimed to analyse selected essays from the anthology Aesthetics of Incompleteness by Shoaib Bin Hassan to prove the intertextual nature of language in the Pakistani postmodern Anglophone literature. The objective was to explore the linguistic and thematic intertextual underpinnings to highlight how literary, cultural, and historical narratives are interwoven in the text, which denotes the absence of a transcendental signified and the text becomes a web of textuality. Using a deconstructionist approach, the study postulated that language bears the absence of a transcendental signified, which marks its decentred nature, complemented by the concept of intertextuality. In this research, the language and referents employed by Hassan in his essays were specifically analysed. This study fills the research gap that appears in contemporary Pakistani Anglophone literature due to a lack of poststructuralist research. The critical ideas propounded by (Derrida, 2009; Catherine Besley, 2008; Peter Barry, 2007; Leitch, 1983; Maria Jesus Martinez Alfaro, 1996) served as the basis of the theoretical framework utilized in this study and secondary texts for this research. Opening up similar poststructuralist viewpoints for the exploration of postmodern literature, this study paves the way for more research on Pakistani Anglophone literature intended to analyse textual innovations, specifically in contemporary texts. Moreover, since literary essay is a withering genre in Pakistani Anglophone literature, this research is likely to play a significant role in rejuvenating its importance and adding a new literary dimension to it.Keywords: decentred, intertextuality, language, transcendental signified